2022
DOI: 10.1002/jsfa.12050
|View full text |Cite
|
Sign up to set email alerts
|

Ridge cropping and furrow irrigation pattern improved spring maize (Zea mays L.) yield and water productivity in Hetao irrigation area of north‐western China

Abstract: BACKGROUND Improving irrigation water productivity is vital for sustaining high maize yield in Hetao irrigated area of northwest China. Whether ridge cropping and furrow irrigation systems (planting both on ridges and in furrows) fulfill water‐saving and maize yield‐increasing is unclear. A 2‐year trial was conducted to reveal the influence of irrigation with three levels (270, 225, 180 mm, represented as I270, I225, I180, respectively) under two planting systems [traditional flat planting system (TFI) and rid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…The ridge-furrow planting pattern had a significant influence on wheat yield. Studies have shown that ridge-furrow planting patterns can effectively promote crop development and increase grain yield [32,33]. The increase in crop yield is affected by the proportion of ridges and furrows.…”
Section: Crop Yield and Yield Componentsmentioning
confidence: 99%
“…The ridge-furrow planting pattern had a significant influence on wheat yield. Studies have shown that ridge-furrow planting patterns can effectively promote crop development and increase grain yield [32,33]. The increase in crop yield is affected by the proportion of ridges and furrows.…”
Section: Crop Yield and Yield Componentsmentioning
confidence: 99%
“…One of the primary reasons that some farmers are engaged in ridge farming systems is that the ridge fields canalize enhanced water flows into the furrow area, which subsequently functions as an infiltration zone [30]. This leads to more efficient irrigation water use and increased crop yield while avoiding salinity and water logging [31][32][33][34]. The reduction of soil compaction caused by machinary traffic in the tree row, which can be particularly significant in young orchards, is the other advantage of the ridge system [35].…”
Section: Introductionmentioning
confidence: 99%